Study Macrozoobenthos at Batu Asahan Coastal Zone of IV Jurai District of Pesisir Selatan Regency The West Sumatera Province - Giovano Aldizia; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in November 2016 in the area at Batu Asahan coastal zone of IV Jurai district of Pesisir Selatan regency the West Sumatra Province, aim at determine the community structure of macrozoobenthos. Sampling using transect method squares and samples were analyzed at the Marine Biological Laboratory of the Faculty of Fisheries and Marine Sciences, then presented and discussed descriptively with various references. Based on the research of macrozoobenthos abundance is highest was at station 1 92.00 ind / m², and was lowest abundance at the station 3 is 9.20 ind / m². Found four classes of macrozoobenthos are gastropods, Malacostraca, Maxillopoda, and Ophiuroidae, where gastropods eight species, one species Malacostraca, one species Maxillopoda and one species Ophiuroidae. Species diversity index values ranging between 1.685 - 2.057, the dominance index ranges from 0.30676 - 0.45963, uniformity index ranging between 0.78784 - 0.99344. Batu Asahan waters condition based on water quality parameters measured was able to support the life in particular macrozoobenthos and marine organisms in general.Keywords: Macrozoobenthos, Abundance, Batu Asahan Beach, West Sumatera